PENGARUH GAYA PENGASUHAN TERHADAP KEPERCAYAAN DIRI SISWA DALAM KONTEKS PENDIDIKAN INKLUSIF - Fauziah Nasution; Tazkiya Aulia Ibriza; Anggun Siska Pratiwi; Sahmiral Amri Raja Guk Guk (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2023)
Inclusive education emphasizes fairness, equality and recognition in the educational environment. Students’ self-confidence is important for improving their participation and achievement. This study examined the influence of parenting style on students’ selfconfidence in inclusive education. The quantitative study involved 200 students from inclusive schools in North Sumatra. Questionnaires were used to measure parenting styles and students’ self-confidence. Regression analysis showed that authoritative parenting style had a positive and significant effect on students’ self-confidence, while permissive and authoritarian parenting styles were not significantly related. It is important for educators and parents to pay attention to parenting styles that support the development of students’ self-confidence in inclusive education. Future research could look at other factors that influence students’ self-confidence and extend to a wider geographical area.